Clinical, biochemical, and phenotype profile of the patients newly diagnosed with polycystic ovarian syndrome - Vikrant Ghatnatti; Shwetha Patil; Harpreet Kour; Ashok Kumar Bhuyan; Bipul Kumar Choudhary; Uma Kaimal Saikia; Dipti Sharma (Wolters Kluwer Medknow Publications, 2021)
OBJECTIVES: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women of reproductive age. This study was aimed to assess the clinical, biochemical, and phenotypic profile of patients newly diagnosed to have PCOS. SUBJECTS AND METHODOLOGY: A cross-sectional study was conducted for a period of 1 year in the Department of Endocrinology, Guwahati Medical College and Hospital. A total of 50 female patients newly diagnosed to have PCOS by the Rotterdam criteria 2003 were enrolled for the study. Clinical Characteristics, thyroid profile, other hormonal tests, oral glucose tolerance test, and phenotypic assessment were done. RESULTS: Twenty-four percent of patients had dysglycemia, while the rest 76% had normal glucose levels. Glucose abnormalities were noted in 13.7% of lean PCOS and 32.2% of overweight PCOS. There was no difference in insulin resistance among the three phenotypes of PCOS. CONCLUSION: Women with PCOS are at increased risk of developing glucose intolerance and diabetes. Dysglycemia in PCOS women was mainly evident in postglucose challenge glucose levels. Since there is no difference in insulin resistance among various phenotypes, all the phenotypes equally merit screening for glucose abnormalities.